Aero-acoustics noise assessment for Wind-Lens turbine. (1st January 2017) - Hashem, I.; Mohamed, M.H.; Hafiz, A.A.
Abstract: This paper introduces an aero-acoustic computational study that investigates the noise caused by one of the most promising wind energy conversion concepts, namely the "Wind-Lens" technology. The hybrid method - where the flow field and acoustic field are solved separately, was deemed to be an appropriate tool to compute this study. The need to investigate this phenomenon increased gradually, since the feasibility of utilizing Wind-Lens turbine within densely populated cities and urban areas depends largely on their noise generation. Ffowcs Williams-Hawkings (FW-H) equation and its integral solution are used to predict the noise radiating to the farfield. CFD Simulations of transient three-dimensional flow field using (URANS) unsteady Reynolds-averaged Navier-Stokes equations are computed to acquire the acoustic sources location and sound intensity. Then, the noise propagates from the before-mentioned sources to pre-defined virtual microphones positioned in different locations. ANSYS-FLUENT is used to calculate the flow field on and around such turbines which is required for the FW-H code. Some effective parameters are investigated such as Wind-Lens shape, brim height and tip speed ratio. Comparison of the noise emitted from the bare wind turbine and different types of Wind-Lens turbine reveals that, the Wind-Lens generates higher noise intensity. Highlights: Aero-acoustic noise generated by wind turbines are one of the major challenges. Noise from wind turbine equipped with a brimmed diffuser is investigated. A computational aero-acoustic study using the hybrid method is introduced. Effective parameters are studied such Wind-Lens shape, brim height and speed ratio. The optimal shape has a moderate power coefficient and the less noise generation.